Hubungan Fear Of Missing Out (FoMO) dengan Tingkat Religiusitas Remaja Muslim Generasi Z pada Siswa SMA di Bogor - Muhamad Hafiz; Muhammad Rifal Shaumi (Jurnal Budi Pekerti Agama Islam, 2026)
The development of digital technology has changed the lifestyle patterns, social interactions and psychological conditions of adolescents. One of the psychological phenomena that exist in adolescent social media users is Fear of Missing Out (FoMO), which is a condition where a person feels anxious if they do not know the activities of others through social media. Religion is present to help individuals gain psychological peace. This study was conducted to determine the level of religiosity and FoMO in Muslim adolescents of Generation Z, and to analyze the relationship between the two. This research method uses a quantitative approach with a correlational research type. The results of the study show a negative relationship between religiosity and the level of Fear of Missing Out (FoMO) in Muslim adolescents of Generation Z who use social media. Adolescents who have a high level of religiosity are able to control digital behavior and reduce the tendency to experience social anxiety due to social media. Meanwhile, adolescents who are active in using social media and have a dependence on digital devices, most are still able to control the digital social anxiety they experience.